PENGARUH INSENTIF DAN KESELAMATAN KERJA TERHADAP MOTIVASI DAN KINERJA KARYAWAN PADA PT. AMTEK ENGINEERING BATAM - HENDRA SIBARANI; NANDA HARRY MARDIKA (LP2MTBM MAKARIOZ, 2020)
The aim of this study is to study and evaluate the motivation, job security and motivation of employees in PT. Amtek Batam Engineering and note what changes to suppor. The results of the analysis using SPSS Version 22 are displayed incentives, Work safety and protection positive motivation Employee performance information. Test Results with t Test Shows incentive variables are positive and significant variables On the Performance of Employees in PT Mtech Engineering Batam. From the above comments, it is forwarded to the forwarding companies and streams copied from company to company, company and company will be happy, so employees will be happy to work. Companies and they can improve the company. Motivation given to employees is further encouraged and provides positive direction to employees, in terms of giving awards, attention, competition, participation, pride, and fighting that are justly agreed to each employee. This does not allow for social jealousy between employees and can improve performance. Good incentives and motivational support increase productivity and improve employee performance.